Identifikasi kepribadian siswa sekolah dasar dalam pembelajaran PJOK berdasarkan Teori Carl Jung - Imam Sugeng; Arika Umi Zar’in; Rendhitya Prima Putra; Nur Ahmad Muharram (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to identify the personality types of elementary school students who participate in Physical Education, Sports, and Health (PJOK) learning based on Carl Jung's theory. The study used a qualitative descriptive method with the subjects of 26 grade VI students at MI Darul Huda Umbulsari Jember for the 2025/2026 school year. Data collection was carried out through observation and personality tests using the Potensiku application. Data analysis was carried out using the percentage technique. The results showed that most students had extroverted personality types as many as 21 students (80.77%), while 5 students (19.23%) were introverts. These findings are reinforced by personality test results that show the dominance of extroverted personality types. In addition, students who take part in PJOK learning tend to be more active in physical activities and show more prominent achievements in the field of sports skills than academic achievements. Thus, it can be concluded that PJOK learning is related to extroverted personality tendencies in elementary school students, so understanding of students' personality types is important to support effective PJOK learning planning and according to student characteristics.